2015
DOI: 10.21657/tsd.36165
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of nitric oxide and thiourea regulates on growth and some key physiological processes in maize (Zea mays L.) plants under saline stress.

Abstract: Effect of exogenously applied nitric oxide (NO) and thiourea (TU) in combination was examined in maize plants under saline stress. Seedlings of two maize cultivars (DK 5783 and Apex 836) were grown in pots containing soil salinized with 0 or 100 mM NaCl dissolved in irrigation water. Two levels of NO + TU (3 + 400 or 6 + 500 mg/L) were applied as presowing seed treatment or through leaves of 10-day old maize seedlings. Saline stress significantly suppressed plant fresh biomass, leaf water potential and chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Accumulation of essential nutrients within plant cells/tissues is one of the primary requisites for the smooth functioning of plant metabolic processes (Kaya et al, 2014). In the present study, B toxicity lowered down leaf Ca 2+ , N and K + contents in the tomato plants, but foliar-applied NO increased these mineral nutrients in the Bstressed plants.…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…Accumulation of essential nutrients within plant cells/tissues is one of the primary requisites for the smooth functioning of plant metabolic processes (Kaya et al, 2014). In the present study, B toxicity lowered down leaf Ca 2+ , N and K + contents in the tomato plants, but foliar-applied NO increased these mineral nutrients in the Bstressed plants.…”
Section: Discussionmentioning
confidence: 38%
“…Nitric oxide (NO) is an endogenous signaling molecule and its exogenous application seems to be a reasonable strategy to overcome damages from stresses (biotic/abiotic) in different crops (Xie et al, 2008;Yildiztugay et al, 2014;Kaya et al, 2014;Zhang et al, 2014). We observed that foliar-applied NO partly increased fruit yield (quantity/weight) of tomato plants subjected to B toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective role of NO treatment was tested in various plants such as tomato, pepper, wheat, barley, rice, maize, soybean, mangrove, or chamomile (Li et al 2008 ;Zheng et al 2010;Fallahi and Khajeh Hosseini 2011 ;Nalousi et al 2012 ;Nasrin et al 2012 ;Simaei et al 2012 ;Kausar et al 2013 ;Ali and Ismail 2014 ;Chen et al 2014 ;Egbichi et al 2014 ;Habib and Ashraf 2014 ;Manai et al 2014 ;Kaya et al 2015 ;Sanam et al 2015 ). In studies conducted by Ali and Ismail ( 2014 ), the application of NO (10 μM of sodium nitroprusside) improved tomato fruit quality in the face of salinity (100 mM NaCl) by enhancing the synthesis of health-promoting compounds ( phenolic compounds, fl avonoids, and alkaloids) in tomato fruits along with signifi cant changes in other quality parameters.…”
Section: Effect Of Exogenous Application Of Nitric Oxide Under Salinitymentioning
confidence: 99%
“…After the application of phytohormones + SNP, the activities of polyphenol oxidase and phenylalanine ammonia lyase increased, thus reducing the damaging effects of salt stress by enhancing the activity of antioxidative systems. Kaya et al ( 2015 ) tested the effect of NO + thiourea (TU) treatment (two levels of NO + TU: 3 + 400 mg/L and 6 + 500 mg/L) as seed soaking treatment and foliar application in two maize cultivars (Apex 836 and Dk 5783) under salinity conditions (100 mM NaCl). Seed treatment was more effective than foliar application in terms of improvement in fresh weight.…”
Section: Effect Of Exogenous Application Of Nitric Oxide Under Salinitymentioning
confidence: 99%